KARAKTERISASI ALAT PIROLISIS ASAP CAIR MENGGUNAKAN VARIASI LIMBAH TONGKOL JAGUNG DAN AMPAS TEBU - Shafwan Amrullah; Cyrilla Octaviananda (JURNAL TEKNOLOGI PERTANIAN, 2023)
Food preservation is currently an important focus, this is due to the food crisis which is worrying. Various techniques have been developed to overcome this, one of which is the preservation of manakan. This is necessary as an appropriate step in maintaining the shelf life. One of the most popular techniques today is the use of liquid smoke, because liquid smoke can be used safely and inexpensively. In this research, the process of characterizing liquid smoke made using agricultural waste, namely corn cobs and bagasse. This research was conducted by mixing the raw materials for corn cobs: bagasse (100:0 (V1); 70:30 (V2); 50:50 (V3)). The tool used is a self-designed pyrolysis tool. The results obtained are the characterization of liquid smoke products showing that the best treatment is in the 50:50 raw material formulation, namely with a yield of 1.8%, pH 2.5, and specific gravity is 1.0225. While the results of the GC-MS test showed that the acetic acid content produced was 49.76%. The smoke color in this formulation is reddish brown without any suspended matter. Based on these results, the 50:50 formulation can meet the Indonesian National Standard (SNI) for liquid smoke.